PENERAPAN MODEL PEMBELAJARAN TEMATIK UNTUK MENINGKATKAN HASILBELAJAR SISWA KELAS 1b SD NEGERI 101 PEKANBARU - Doharni '; Erlisnawati '; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the above issues, we need a model that can enable all the students in the learning process. One model of learning that can make students active and easy to remember the subject matter is the implementation of thematic learning model. Tepadu thematic learning is learning that uses a theme to link several subjects so as to provide a meaningful experience to the students. Integrating thematic learning between the experiences to other experiences or knowledge with the knowledge of one another and even between the experience with the knowledge and instead give meaningfulness in learning in the sense that it gives learning a useful function for the life of the student. For that in this classroom action research aims to improve student learning outcomes Ib grade Elementary School 101 TP Pekanbaru city. 2014/2015 using thematic learning model implemented on 3.5 March 9 for the first cycle and the date 17,19,23 March for the second cycle. The subjects were students of class IB Elementary School 101 Pekanbaru totaling 30 students parameter student is student learning, mastery learning students, student activities and teacher. The results showed that the learning outcomes have increased. In the first cycle the average completeness of students is 66.67% (incomplete) and the second cycle of 83.33% (completed). On an average student activity at the first meeting of 66.67% with the good category, the second meeting 75% with the good category, the third meeting 83.3% with very good categories and the fourth meeting of 100% with very good category. On average activity of teachers at the first meeting of 66.67% with the good category, the second meeting 75% with the good category, the third meeting 83.3% with very good categories and the fourth meeting of 91.7% with very good category. From the results of this study concluded that using Thematic learning model can improve student learning outcomes IB Elementary School class 101 Pekanbaru. Researchers propose the following suggestions:1. With the implementation of thematic learning in the learning process, the learning outcomes of students of class 1B SDN 101 Pekanbaru city will increase. 2 With the implementation of thematic learning, then learning quality SDN 101 Pekanbaru city will be increased, the activity of teachers and students also will increase with applied thematic learningKey words : thematic learning, students grade achievement2